Climate Change Litigation: Chronicles from the Global South. A Comparative Study - Kavuri, Sudha; Ramanathan, Anjana (Comparative Law Review, 2022)
The battles against climate change are being fought at the international level; on the domestic front; on the streets and in the courts. Climate change litigation is one such effort. The global expansion in climate litigation gives substance to claims of a transnational climate justice movement that casts courts as important players in shaping multilevel climate governance. Climate change litigants, lawyers, and judges of one country are taking their cue from their counterparts in other countries. However, only the efforts of the Global North have received prominence. The rest of the world is slated to be sleeping silently. The authors aim to de-bunk this myth. In doing so, the authors endeavour to highlight important contributions by the Courts in the Global South in furthering the jurisprudence of climate change litigation.